The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/fst.36719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum packaging on artisanal goat cheeses during refrigerated storage

Abstract: The aim of the present work was to investigate the effects of vacuum packaging and storage time on physicochemical composition, fatty acid content, color, microbiological content and rheological behavior of artisanal fresh goat cheese during refrigerated storage. The results show that both vacuum packaging and storage time had an influence on moisture content, color variation and rind formation, obtaining better visual appearance and higher moisture content in vacuum packed cheeses. The packaging also positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
2
7
0
1
Order By: Relevance
“…The absence of significant metabolitic transformation of fatty acid at low temperature was in good agreement with slow proteolysis observed in these samples (Figure 1, Table 2). Similar trends were observed by Frau et al (2021) during refrigerated storage of artisanal goat cheese. As a result of slow metabolitic transformation of fatty acids, samples ripened at low temperature are characterized with similar health fatty acid indices.…”
Section: Fatty Acid Profiles and Health Fatty Indices Of Kajmaksupporting
confidence: 83%
“…The absence of significant metabolitic transformation of fatty acid at low temperature was in good agreement with slow proteolysis observed in these samples (Figure 1, Table 2). Similar trends were observed by Frau et al (2021) during refrigerated storage of artisanal goat cheese. As a result of slow metabolitic transformation of fatty acids, samples ripened at low temperature are characterized with similar health fatty acid indices.…”
Section: Fatty Acid Profiles and Health Fatty Indices Of Kajmaksupporting
confidence: 83%
“…Silva et al (2017) reported that Minas fresh cheeses can be handmade on small farms with raw milk, without proper hygiene control, resulting in a product with high levels of bacterial contamination, including S. aureus and coliforms. Frau et al (2021) described that most of the cheese manufactured and sold in the in the north of Argentina is artisanal fresh cheese and is usually made by farmers on a small scale in their farmhouse, using traditional techniques. The final product has a high moisture content (50 to 65%), a low pH (4.1 to 4.5), and a short shelf life (< 30 d).…”
Section: Resultsmentioning
confidence: 99%
“…Tang et al (2017) found that, compared with raw catfish slices, cooking of catfish at 70 °C for 5 min followed by refrigeration can significantly delay increase in TVB-N content and inhibit growth of microorganisms during storage, thereby prolonging shelf life of catfish meat by twelve days. Since SV employs vacuum and sealing in a plastic bag, an anaerobic environment is formed during heating treatment and subsequent storage, which can effectively prevent bacteria growth (Frau et al, 2021;Yehia et al, 2020). Moreover, compared to conventional heating, the synergistic effect of vacuum packaging and heating employed during SV was shown to lead to a three-log reduction in bacterial load in shrimp (Mohan et al, 2017).…”
Section: Impact On Safety Of Aquatic Food Productsmentioning
confidence: 99%